Chronic Obstructive Pulmonary Disease and Small Airways Diseases - Elicker, Brett M. (Seminars in Respiratory and Critical Care Medicine, 2022)
The small airways are a common target of injury within the lungs and may be affected by a wide variety of inhaled, systemic, and other disorders. Imaging is critical in the detection and diagnosis of small airways disease since significant injury may occur prior to pulmonary function tests showing abnormalities. The goal of this article is to describe the typical imaging findings and patterns of small airways diseases. An approach which divides the imaging appearances into four categories (tree-in-bud opacities, poorly defined centrilobular nodules, mosaic attenuation, and emphysema) will provide a framework in which to formulate appropriate and focused differential diagnoses.
Keywords: diffuse lung disease; small airways diseases; tree-in-bud opacities; mosaic attenuation; emphysema and chronic bronchiolitis